Automaticity and Stability of Adaptation to a Foreign-Accented Speaker. (June 2015) - Witteman, Marijt J; Bardhan, Neil P; Weber, Andrea; McQueen, James M
In three cross-modal priming experiments we asked whether adaptation to a foreign-accented speaker is automatic, and whether adaptation can be seen after a long delay between initial exposure and test. Dutch listeners were exposed to a Hebrew-accented Dutch speaker with two types of Dutch words: those that contained [ɪ] (globally accented words), and those in which the Dutch [i] was shortened to [ɪ] (specific accent marker words). Experiment 1, which served as a baseline, showed that native Dutch participants showed facilitatory priming for globally accented, but not specific accent, words. In experiment 2, participants performed a 3.5-minute phoneme monitoring task, and were tested on their comprehension of the accented speaker 24 hours later using the same cross-modal priming task as in experiment 1. During the phoneme monitoring task, listeners were asked to detect a consonant that was not strongly accented. In experiment 3, the delay between exposure and test was extended to 1 week. Listeners in experiments 2 and 3 showed facilitatory priming for both globally accented and specific accent marker words. Together, these results show that adaptation to a foreign-accented speaker can be rapid and automatic, and can be observed after a prolonged delay in testing.